Throughput optimization of the cipher message authentication code - Selimis, G.; Michail, Harris; Kakarountas, A. P.; Goutis, C. E. (My University, 2007)
A new algorithm for producing message authenticating code (MAC) was recently proposed by NIST. The MAC protects both a message's integrity - by ensuring that a different MAC will be produced if the message has changed - as well as its authenticity - because only someone who knows the secret key could be able to generate a valid MAC. The proposed process incorporates a FIPS approved anti secure block cipher algorithm which was standardized by NIST in May, 2005. The first implementation of the CMAC is presented in this paper. Throughput has been the main design target. The proposed implementation goes one step further introducing an optimized ciphering core to achieve competitive throughput for CMAC, compared to alternative MACs. © 2007 IEEE.
Keywords: Hardware implementation; Message authentication code